Floodplains provide important amphibian habitat despite multiple ecological threats - Holgerson, Meredith A.; Duarte, Adam; Hayes, Marc P.; Adams, Michael J.; Tyson, Julie A.; Douville, Keith A.; Strecker, Angela L. (Ecosphere (Washington, D.C), 2019)
Floodplain ponds and wetlands are productive and biodiverse ecosystems, yet they face multiple threats including altered hydrology, land use change, and non‐native species. Protecting and restoring important floodplain ecosystems requires understanding how organisms use these habitats and respond to altered environmental conditions. We developed Bayesian models to evaluate occupancy of six amphibian species across 103 off‐channel aquatic habitats in the Chehalis River floodplain, Washington State, USA. The basin has been altered by changes in land use, reduced river–wetland connections, and the establishment of non‐native American bullfrogs (Rana catesbeiana = Lithobates catesbeianus) and centrarchid fishes, all of which we hypothesized could influence native amphibian occupancy. Despite potential threats, the floodplain habitats had relatively high rates of native amphibian occupancy, particularly when compared to studies from non‐floodplain habitats within the species’ native ranges. The biggest challenge for native amphibians appears to be non‐native centrarchid fishes, which strongly reduced occupancy of two native amphibians: the northern red‐legged frog (Rana aurora) and the northwestern salamander (Ambystoma gracile). Emergent vegetative cover increased occupancy probability for all five native amphibian species, indicating that plant management may offer a strategy to counter the negative effect of centrarchids by providing refuge from predation. We found that temporary and permanent hydroperiod sites supported different species; hence, both should be conserved on the landscape. Lastly, human‐created and natural ponds had similar amphibian occupancy patterns, suggesting that pond construction offers a viable strategy for adding habitats to the floodplain landscape. Overall, floodplain ponds and wetlands provide important amphibian habitat, and we offer management strategies that will bolster amphibian occupancy in an altered floodplain landscape.